An Investigation into Loss and Gain in the Translation of Rhetorical Questions from English into Vietnamese - Nguyễn Thị Thanh Hương (2012)
This thesis has been done in an effort to investigate the transferring of rhetorical questions in translated works of modern literature from English into Vietnamese, employing the theoretical perspectives suggested by Barnwell [11]. A…..